The Empowerment Model of Clinical Supervision and Its Application to Standardization of Financial Therapy Supervision - Khara Croswaite Brindle (Journal of Financial Therapy, 2023)
Financial therapy creates a meaningful bridge between mental health and money, which indicates a complex framework in support of clients and financial therapists alike. Recognizing the newness of financial therapy as a profession, adopting a supervision style for financial therapists that can support the integrity and ethics of the profession, as well as define the growth opportunities of financial therapists called to do this meaningful work, is of utmost importance. The Empowerment Model of Clinical Supervision, with its focus on self of the therapist and empowerment of supervisees, can serve as a template for the standardization of financial therapy supervision.
Keywords: Self of financial therapist; financial therapy supervision; financial therapy supervisor